Dialetika Pancasila, Ideologi, dan Kehidupan Beragama - H. Mashudi (PAX HUMANA, 2015)
Pancasila is the idea and the ideology that absolutely must be owned and embedded in each of the in and out of activity The Unitary State of the Republic of Indonesia. Addresing the very complex issue of the nation, it is required the cooperation of various parties and also a product of legislation to guard the life of the nation. This article intends to explain the various approaches that must be considered in solving the nations problems mainly related to ideologies that could destroy the nation such as terrorism. Finally, at the end of this paper, also included some solutions in an attempt to resolve these issues primarily related to religious diversity. Keywords: Pancasila, Ideology, Religion